2013
DOI: 10.1253/circj.cj-12-0647
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Aryl Hydrocarbon Receptor Mediates Indoxyl Sulfate-Induced Monocyte Chemoattractant Protein-1 Expression in Human Umbilical Vein Endothelial Cells

Abstract: Circulation Journal Official Journal of the Japanese Circulation Society http://www. j-circ.or.jp positive correlation between chronic kidney disease (CKD) and cardiovascular disease (CVD) has been demonstrated, but the causative role of uremic toxin remains unclear. 1-3 A number of retention compounds act as uremic toxins, accumulating in the blood of CKD patient, and elevated circulating uremic toxins negatively affect biological function through induction of oxidative stress. The removal of uremic solutes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
76
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(82 citation statements)
references
References 41 publications
4
76
1
1
Order By: Relevance
“…At present, kynurenine, kynurenic acid, indoleacetic acid, and indoxyl sulfate-all indolic products of tryptophan metabolism-have been shown to bind to the AhR or induce the expression of AhR response genes, such as CYP1A1. 38,[93][94][95][96][97] Moreover, as shown in Table 3, all four metabolites activate the AhR at concentrations either similar to the highest C max determined in dialysis patients (eg, indole acetic acid) or at levels decisively lower than the C max , for instance indoxyl sulfate. To date, the clinical implications of AhR activation in the setting of CKD development and progression remain unclear, however, it has been postulated that uremic solutes might evoke dioxinlike toxicity, 38 leading to suppression of immune responses, induction of carcinogenesis and accelerating tumor growth, and promoting atherosclerosis.…”
Section: Intracellular Fate Of Uremic Toxinsmentioning
confidence: 83%
“…At present, kynurenine, kynurenic acid, indoleacetic acid, and indoxyl sulfate-all indolic products of tryptophan metabolism-have been shown to bind to the AhR or induce the expression of AhR response genes, such as CYP1A1. 38,[93][94][95][96][97] Moreover, as shown in Table 3, all four metabolites activate the AhR at concentrations either similar to the highest C max determined in dialysis patients (eg, indole acetic acid) or at levels decisively lower than the C max , for instance indoxyl sulfate. To date, the clinical implications of AhR activation in the setting of CKD development and progression remain unclear, however, it has been postulated that uremic solutes might evoke dioxinlike toxicity, 38 leading to suppression of immune responses, induction of carcinogenesis and accelerating tumor growth, and promoting atherosclerosis.…”
Section: Intracellular Fate Of Uremic Toxinsmentioning
confidence: 83%
“…We therefore examined the effects of AhR blockade on cellular senescence. Pretreatment with ANF (10 μmol/L) or CH223191 (10 μmol/L) 39) , AhR inhibitors, for one hour rescued the IS-induced cellular senescence in the HUVECs (Fig. 3A).…”
Section: Is-induced Endothelial Senescence Is Ahrdependentmentioning
confidence: 95%
“…It has been reported that the mechanism by which IS induces oxidative stress involves the transport of IS into the cell via organic anion transporters (OAT1, OAT3), where it then activates nicotinamide adenine dinucleotide phosphate (NADPH) oxidase in endothelial, renal tubular and glomerular mesangial cells [34][35][36][37][38] . Although it is unknown how IS activates NADPH oxidase, we recently found that aryl hydrocarbon receptor (AhR), which is expressed in human umbilical vein endothelial cells (HUVECs), is involved in the upregulation of NADPH oxidase-4 induced by IS 39) . AhR is a ligand-activated nuclear receptor/transcription factor belonging to the basic helix-loophelix/per-AhR nuclear translocator (ARNT)-Sim fam-mined using a Nampt colorimetric assay kit (CycLex) according to the manufacturer's instructions.…”
Section: Cell Culturementioning
confidence: 99%
See 2 more Smart Citations